Combined Association of Serum Uric Acid and Metabolic Syndrome with Chronic Kidney Disease in Hypertensive Patients - Haijiang Dai; Shijuan Lu; Xiaohong Tang; Minggen Lu; Ruifang Chen; Zhiheng Chen; Pingting Yang; Chang Liu; Honghao Zhou; Yao Lu; Hong Yuan (Karger Publishers, 2016)
Background/Aims: Chronic kidney disease (CKD) is one of the major complications of hypertension. It is not only associated with the future burden of end-stage renal disease but also affects mortality and cardiovascular outcomes caused by hypertension. To help understand the pathogenesis and early prevention of progressive CKD, this large-scale study is designed to determine the complex association between serum uric acid (SUA), metabolic syndrome and the prevalence of CKD in hypertensive patients. Methods: A total of 19,848 hypertensive subjects were enrolled in this cross-sectional study. Patients with proteinuria and/or an estimated glomerular filtration rate (eGFR) of 2 were considered CKD cases. Results: Hypertensive subjects with CKD had a higher prevalence of hyperuricemia and metabolic syndrome, as well as higher levels of SUA, BMI, waist circumference (WC), SBP, DBP, TG, fasting blood glucose and lower levels of HDL-C. Compared to patients without CKD, the multivariate-adjusted odds ratios [ORs, 95% confidence interval (CI)] for CKD patients were 2.30 (2.02-2.63) for hyperuricemia, 1.21 (1.04-1.41) for abdominal obesity, 1.21 (1.06-1.38) for elevated TG, 1.29 (1.06-1.56) for low HDL-C, 1.54 (1.36-1.75) for elevated fasting glucose, and 1.49 (1.30-1.71) for metabolic syndrome. Increasing SUA levels and number of individual metabolic syndrome components were associated with an increased prevalence of CKD. Compared with patients classified in the lowest SUA categories and with ≤1 metabolic syndrome components, subjects with HUA and 4 metabolic syndrome components had a 5.77-fold increased OR for CKD based on the multivariate-adjusted analysis. Conclusion: Both elevated SUA and metabolic syndrome are associated with an increased prevalence of CKD in hypertensive subjects. Subjects with higher SUA and sum of individual metabolic syndrome components simultaneously have a higher prevalence of CKD.